Post-Operative Neurological Outcome of Intradural Spinal Tumors in Terms of Improvement In Mccormick’s Classification Scheme - Hassan, Naseer; Ali, Mehran; Ahmad, Mansoor; Rehman, Hanif Ur; Tahir, Hamayun; Hassan, Raza; Kabir, Samir Khan (Journal of Gandhara Medical and Dental Science, 2021)
OBJECTIVES: To determine the post-operative neurological outcome of intradural spinal tumors in terms of improvement in McCormick classification scheme. METHODOLOGY: Total of 95 patients diagnosed as case of intradural spinal tumor as per operational definition with any McCormick grade were analyzed. After admission and complete neurological examination, pre-operative McCormik’s grades of each patient were determined and followed for one month after surgery. During their stay they were assessed for neurological improvement as per McCormick grade. RESULTS: There were total 95 patients presenting in OPD with the mean age of 45±12.36 years. There were 42% male and 58% female. There were 62% patients who were improved in neurological outcome while 38% patients were not improved. CONCLUSION: Surgical removal of spinal tumor is beneficial to the affected individual and has positive effect on his life.